2008
DOI: 10.1038/jhh.2008.141
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and heart failure: a dysfunction of systole, diastole or both?

Abstract: The pathological myocardial hypertrophy associated with hypertension contains the seed for further maladaptive development. Increased myocardial oxygen consumption, impaired epicardial coronary perfusion, ventricular fibrosis and remodelling, abnormalities in long-axis function and torsion, cause, to a varying degree, a mixture of systolic and diastolic abnormalities. In addition, chronotropic incompetence and peripheral factors such as lack of vasodilator reserve and reduced arterial compliance further affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 127 publications
(143 reference statements)
1
26
0
2
Order By: Relevance
“…28) Some studies showed that heart rate response was blunted in hypertensive patients with or without heart failure. 29) Our present study also demonstrated that the nondiagnostic group had higher BMI and more hypertension than the negative group. Study limitations: First, our study was limited by a crosssectional rather than a longitudinal design.…”
Section: Discussionsupporting
confidence: 68%
“…28) Some studies showed that heart rate response was blunted in hypertensive patients with or without heart failure. 29) Our present study also demonstrated that the nondiagnostic group had higher BMI and more hypertension than the negative group. Study limitations: First, our study was limited by a crosssectional rather than a longitudinal design.…”
Section: Discussionsupporting
confidence: 68%
“…While blood pressure reduction is a major treatment goal in hypertensive heart disease, reducing ischemia and reversing pathological remodeling are key to preventing mortality and morbidity due to diastolic dysfunction (29). Recent evidence from work using bone marrow mononuclear cells (BMMNC) to treat myocardial infarction has shown a robust proangiogenic and antifibrotic effect of exogenous BMMNC therapy in ischemic hearts (8).…”
mentioning
confidence: 99%
“…Markers of collagen turnover and extracellular matrix proliferation cause detectable changes in left ventricular compliance and longitudinal axis mechanics and function even before LVH is detectable [8,9]. This remodeling of the extracellular matrix is thought to be pivotal in causing abnormalities of ventricular relaxation and ventricular compliance that characterize diastolic dysfunction, and it occurs in association with myocyte hypertrophy or independent of the development of LVH [19,23]. In patients with LVH, myocardial fibrosis is particularly increased in the subendocardial region [24].…”
Section: Potential Mechanisms For Impairment Of Diastolic Function Inmentioning
confidence: 96%
“…Furthermore, there is a decrease in capillary density in the hypertrophied ventricle and a reduction in myocardial flow reserve. These factors are thought to predispose to myocardial ischemia even in the absence of epicardial coronary stenosis [4,19]. In addition, there is clustering of hypertension and other atherogenic and dysmetabolic risk factors such as obesity, sleep apnea, and dysmetabolic syndrome that directly and indirectly impair left ventricular function.…”
Section: Potential Mechanisms For Impairment Of Diastolic Function Inmentioning
confidence: 98%